Conflict behavior in elite show jumping and dressage horses - Gorecka-Bruzda, A.; Kosinska, I.; Jaworski, Z.; Jezierski, T.; Murphy, J. (Journal of Veterinary Behavior Clinical Applications and Research, 2015)
Conflict behavior (CB) is a response exhibited by animals that experience difficulty coping with mental or physical discomfort and is most often demonstrated as some form of resistance to handling or training cues and/or equipment. In equestrian sport, Fédération Equestre Internationale (FEI) code of conduct for the welfare of the horse stipulates that "… horses must only undergo training that matches their physical capabilities and level of maturity for their respective disciplines." The objective of this study was to determine the incidence of CB in horses participating in elite equestrian competition. The behavior of 150 horses (N = 100 during show jumping and N = 50 during dressage top-level competitions) was monitored via FEI TV transmissions. We assessed the occurrence of specific CBs in each horse including head shaking, pulling the reins out of the rider's hands (PR), gaping, and tail swishing (TS) per second during competition. In jumping competitions, the CB occurrence associated with each type of obstacle (fence) was divided by the total number of obstacles of that same type. In dressage competition, CB occurrence associated with a given dressage movement was divided by total time (pooled duration in seconds) associated with the movement. Percentage of the time where each horse presented with low head position and with the nose behind the vertical was also recorded. The data indicated that jumping and dressage competitions differed in the occurrence of studied CB per second of the course or test (head shaking, P = 0.0279; PR, P < 0.0001; TS, P < 0.0001, and gaping, P < 0.0001). In show jumping, PR was most frequent and vertical and combination fences were the more problematic obstacles. In dressage, TS was most frequent, whereas other CBs occurred only sporadically. Although TS was observed significantly more often during the complicated dressage movement phases compared with less complicated movement phases, there were no differences in the occurrence of CB in particular movements within the groups of more and less complicated dressage movement phases. Dressage horses were ridden more often (P < 0.0001) in low head position and with nose behind the vertical compared to show jumping horses. Both the percentage of time with head in low position and the nose behind the vertical were positively correlated (rs = 0.50; P = 0.0002) although there was no relationship between these parameters and the occurrence of CB in either jumping or dressage. However, the high incidence of CB observed in elite jumping and dressage competition suggests that many horses may not be sufficiently prepared for competition in line with the FEI code of conduct guidelines. Clearly, this could lead to welfare concerns for the horses within these equestrian disciplines. Finally, we suggest that the occurrence and/or the extent of CB exhibited by horses participating in elite jumping and dressage sport require further scrutiny in terms of the FEI code of conduct guidelines.